Typology and Transformation of Traditional Spatial Planning in Balinese Indigenous Villages: The Case of Blahbatuh - Gunawan, I Gusti Ngurah Anom; Sari, Suzanna Ratih; Hasritanto, Bangun IR.; Sukawi , Sukawi (ASTONJADRO, 2025)
The spatial planning of traditional Balinese villages embodies a profound cultural and religious philosophy, ensuring a balance between sacred spaces, residential areas, and public domains. This study investigates the implementation of the Ulu Teben concept within the spatial structure of traditional villages in Blahbatuh, Bali, and its adaptation to modernization and economic shifts. The primary objective is to assess the extent to which Ulu Teben principles have been maintained and to identify key factors driving spatial transformations. A qualitative approach with a case study method is employed, integrating field observations, in-depth interviews with customary leaders and local communities, and document analysis. The research utilizes thematic and spatial analysis, supported by Geographic Information System (GIS)-based mapping to track spatial alterations. Findings indicate that while Ulu Teben remains a foundational principle in traditional village spatial planning, various adaptations have emerged due to population growth, economic pressures, and the expansion of the tourism sector. These changes have led to shifts in land use, including the conversion of sacred zones into residential and commercial areas. The degree of adaptation varies across different traditional villages, demonstrating flexibility in the application of traditional spatial structures. This study concludes that safeguarding traditional spatial planning necessitates a balanced strategy that integrates indigenous wisdom with modern urban planning policies. Strengthening customary regulations, leveraging digital mapping technologies, and promoting active community involvement are crucial measures in preserving the integrity of the Ulu Teben concept amid modernization challenges.